Analisis Fitokimia Daun Gaharu (Aquilaria microcarpa) Sebagai Produk Teh Celup Asal Keerom, Papua - Sufaati , Supeni; Suharno, Suharno; Dirgantara, Septriyanto; Tanjung , Rosye H.R. (Jurnal Biologi Papua, 2024)
This study explores the phytochemical composition and antioxidant potential of Agarwood (Aquilaria microcarpa) leaves from Keerom, utilized in tea bags. Phytochemical analysis of ethanol extracts revealed flavonoids, alkaloids, steroids/triterpenoids, tannin gallate, and saponins. Total phenol content measured at 1.31 g GAE/100 grams, with total flavonoids at 210 mg QE/100 grams. The extract demonstrated robust antioxidant activity with an AAI value of 1.23, surpassing ascorbic acid (AAI value of 13.37). Mangiferin and quercetin were identified among the compounds in the leaves, highlighting their potential health benefits.